Temperature selection and the final thermal preferendum of snow crab (Chionoecetes opilio, Decapoda) from the Barents Sea - Siikavuopio, Sten Ivar; Bakke, Snorre; Sæther, Bjørn-Steinar; Thesslund, Tina; Christiansen, Jørgen Schou (Polar Biology, 2019)
This is a pre-print of an article published in Polar Biology . The final authenticated version is available online at: https://doi.org/10.1007/s00300-019-02530-3. The snow crab ( Chionoecetes opilio ) is an invasive species new to the Barents Sea that expands its geographic range by larval drift and adult migration. To evaluate the potential spreading of the species in the Barents Sea, we investigated temperature selection and the final thermal preferendum (FTP) of nine adult males in a free choice horizontal temperature gradient (~ 1.0–5.5 °C) for 24 h. The crabs displayed clear behavioural thermoregulation – at test start they explored the entire temperature range but eventually gravitated towards a FTP zone of 1.0–1.6 °C (mean 1.4 °C) after 6 h in the gradient. Our tests show that adult male snow crab is limited to cold waters, and suggest a spreading further into the Euro-Arctic shelf seas.